2004
DOI: 10.1038/sj.bjp.0705764
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide (H2S) stimulates capsaicin‐sensitive primary afferent neurons in the rat urinary bladder

Abstract: In the rat isolated urinary bladder, NaHS (30 mM-3 mM) and capsaicin (10 nM-3 mM) produced concentration-dependent contractile responses (pEC 50 ¼ 3.570.02 and 7.170.02, respectively) undergoing dramatic tachyphylaxis. In preparations in which sensory nerves were rendered desensitized (defunctionalized) by high-capsaicin (10 mM for 15 min) pretreatment, neither capsaicin itself nor NaHS produced any motor effect. NaHS-induced contractile effects were totally prevented by the simultaneous incubation with tachyk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
103
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 15 publications
9
103
1
Order By: Relevance
“…Furthermore, in the isolated guinea pig airway, NaSH induced the release of SP and CGRP from sensory nerve terminals, and led to airway constriction through capsaicin and NKR1/NKR2-transient receptor potential vanilloid 1 (TRPV1)-dependent pathways [73,74]. Similarly, in isolated rat bladder [75] and rat detrusor muscle [76], NaSH induced tachykin release from caspaicin-sensitive primary afferent neurons, leading to smooth muscle contraction. Collectively, these studies suggest that induction of neurogenic inflammation could mediate the reported proinflammatory role of H 2 S in inflammatory pathologies.…”
Section: Role For H 2 S In Neurogenic Inflammation?mentioning
confidence: 99%
“…Furthermore, in the isolated guinea pig airway, NaSH induced the release of SP and CGRP from sensory nerve terminals, and led to airway constriction through capsaicin and NKR1/NKR2-transient receptor potential vanilloid 1 (TRPV1)-dependent pathways [73,74]. Similarly, in isolated rat bladder [75] and rat detrusor muscle [76], NaSH induced tachykin release from caspaicin-sensitive primary afferent neurons, leading to smooth muscle contraction. Collectively, these studies suggest that induction of neurogenic inflammation could mediate the reported proinflammatory role of H 2 S in inflammatory pathologies.…”
Section: Role For H 2 S In Neurogenic Inflammation?mentioning
confidence: 99%
“…In the present issue, Patacchini et al (2004) present evidence that in the detrusor muscle of the rat urinary bladder H 2 S produced contractile responses. These responses exhibited marked tachyphylaxis similar to responses to capsaicin, the active principle from chillies that stimulates certain primary afferent neurons to release neuropeptides, in particular tachykinins and calcitonin gene-related peptide (CGRP) (Maggi, 1995).…”
mentioning
confidence: 73%
“…From the results reported by Patacchini et al (2004), the site of action of H 2 S cannot be determined with certainty. However, the observation that the responses to H 2 S exhibited a similar resistance to tetrodotoxin as those to capsaicin indicates that H 2 S predominantly activates the primary afferent nerve terminals directly rather than indirectly via axonal conduction, which involves fast tetrodotoxin-sensitive sodium channels.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Hydrogen sulfi de (H 2 S) is a well-known gas characterized by a peculiar rotten egg smell, representing a primary chemical hazard in natural gas production, in sewage treatment, and in certain industrial manufacturings (Patacchini et al, 2004). Hydrogen sulfi de is recognized to be a potent inhibitor of cytochrome c oxidase, the terminal enzyme of oxidative phosphorylation, and this is generally considered to be its primary mechanism of toxicity in animals (Reiffenstein et al, 1992;Dorman et al, 2002) and in plants (Kumazawa, 1984).…”
Section: Introductionmentioning
confidence: 99%